KAJIAN HUKUM TERHADAP PRAKTIK VICTIM BLAMING DALAM PENANGANAN KASUS PELECEHAN SEKSUAL DI PERGURUAN TINGGI - I PUTU ANDIKA PRATAMA; Putri Suardani Anak Agung; Suardita I Ketut; Satria Wiradharma Sumertajaya I Ketut (Fakultas Hukum Universitas Ngurah Rai, 2026)
The phenomenon of victim blaming in cases of sexual harassment within higher education institutions remains prevalent. Victims are often perceived as the cause or trigger of the harassment committed by perpetrators. This condition reflects a lack of understanding and inadequate victim-centered perspectives in academic environments. This research is a doctrinal study employing a statute approach, a case approach, and a conceptual approach. The enactment of Minister of Education, Culture, Research, and Technology Regulation Number 55 year 2024, along with other laws and regulations governing the protection of victims of sexual harassment, is expected to minimize such cases, particularly within higher education institutions, and to encourage victims to report incidents without fear. Furthermore, the presence of Law Number 31 year 2014 is intended to provide legal protection for victims of sexual harassment, ensuring that they are safeguarded from intervention, discrimination, and victim blaming by certain parties.